Gender Dimensions of Artisanal and Small-Scale Mining : A Rapid Assessment Toolkit - Eftimie, Adriana (World Bank, 2012)
Artisanal and small-scale mining (ASM) is a global reality. It represents a longstanding and important livelihood for more than 100 million men and women around the world. In some places, communities have practiced it for generations; in other places, the prospect of new mineral finds draws large numbers of people suddenly to mining areas. Whether newly begun or long established, ASM has the potential to help men and women out of poverty when conducted in an informed and responsible way. In different communities, different techniques are used, and men and women share different divisions of labor, risks, and opportunities. ASM assessments, and the recommendations for action arising from these, are critical to the objectives of every ASM stakeholder, whether the large-scale mining (LSM) company seeking to improve the outcomes of its corporate social responsibility programs, a government agency or nongovernmental organization (NGO) seeking to fulfill its policy mandate, a microfinance organization promoting small and medium enterprise development in mining areas, or an association of miners seeking to formalize its activities. The toolkit is comprised of six components: introduction to gender and ASM; the gender and ASM framework; gender and ASM tools; the toolkit in practice; resources; and supplemental CD-ROM.